RECONCEPTUALIZING PANCASILA-BASED CITIZENSHIP EDUCATION IN THE DIGITAL AGE: INTEGRATING ARTIFICIAL INTELLIGENCE, DIGITAL ETHICS, AND PROJECT-BASED LEARNING - Damanik, Prince Clinton Immanuel Christian; Mohammad Idham Chaled; Rizki Achmad Husaeni; Anastasia Arta Uli; Feri Dwi Jayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid expansion of artificial intelligence (AI) and digital media is reshaping contemporary civic identity and challenging existing models of citizenship education. Although global citizenship education frameworks increasingly emphasize technological competence, they often lack grounding in local ethical and cultural values, particularly within elementary education where civic identity is first formed. Addressing this gap, this study synthesizes global citizenship theories and digital innovation research to propose an integrated pedagogical framework for Indonesian elementary schools grounded in Pancasila. Following PRISMA 2020 guidelines, this systematic literature review analyzed peer-reviewed studies published between 2017 and 2025 in the Scopus and Web of Science databases. The analysis focused on AI integration in education, digital literacy inequalities, and the role of Pancasila-based ethics in civic learning. The findings indicate that liberal and global citizenship models, when detached from shared moral foundations, risk weakening civic engagement. In Indonesia, structural disparities in AI adoption further highlight the need for an ethical and equitable approach to digital citizenship education. The review identifies Pancasila as a normative ethical framework capable of guiding responsible digital behavior and supporting Sustainable Development Goals 4, 10, and 16. To operationalize these values in elementary classrooms, Project-Based Learning supported by interactive digital modules emerges as an effective strategy for translating abstract civic principles into meaningful digital action. Developing ethically grounded digital citizens therefore requires sustained teacher capacity-building and the systematic integration of Pancasila-oriented, project-based pedagogies.